Coastal dune dynamics and management at the Bushman's River mouth, Kenton-on-Sea - Fraser, Claire (Rhodes University, Faculty of Science, Botany Department, 2005)
A study of the dynamics and functions of a coastal dunefield at the Bushman's River Mouth in Kenton-on-Sea was conducted to provide essential information for the formulation of a management strategy based on an ecosystem approach. Bi-monthly tacheometric surveys were undertaken at the Westbourne Road Car Park dunefield to investigate the sedimentological processes. Changes in the topography, the amount and rate of sand accretion were monitored. Accretion and progradation were the dominant long-term sedimentological processes at the site. Long-term spatial variation in these processes corresponded to the temporal pattern of sedimentation in the river mouth while short-term variation resulted from dynamics inherent to the types of dunes present. Factors affecting aeolian accretion at the site are topography, river mouth configuration, dune types and the presence of vegetation as well as the seasonal wind regime. A vegetation study, recording species present, cover and abundance of the plants along the surveyed transects, was also conducted to examine the progressive establishment of vegetation. Five plant communities were discerned namely, saltmarsh, pioneer, enriched pioneer, open scrub, closed scrub and scrub-thicket communities. The spatial distribution of these communities coincided with the north-westerly development of the sandbank. A successional trend in community change occurred along a gradient of increasing diversity, complexity and age. Initially, autogenic changes wrought by pioneer species facilitated the recruitment and survival of other species and commenced succession at the study site. Multiple successional pathways were discussed in relation to subsequent species establishment that occurred after facilitation. The amalgamation of ecological data with a social study in the form of public perception surveys allowed for a greater understanding of the present interactions between the ecosystem and the demands placed on it. The area primarily functions as a recreational site that offered numerous beach and water-related activities. A lack of information regarding the ecology and management programmes influenced public perception of the environment and management issues in general. Different management perspectives and the use of the information presented in this study were also discussed.
Keywords: Sand dunes -- South Africa -- Management; Sand dune ecology -- South Africa -- Kenton-on-Sea; Coastal ecology -- South Africa -- Kenton-on-Sea; Coastal zone management -- South Africa -- Kenton-on-Sea